A statistical optimization by response surface methodology for the enhanced production of riboflavin from Lactobacillus plantarum–HDS27: A strain isolated from bovine milk - Hemalatha, M.; Subathra Devi, C. (Frontiers in Microbiology, 2022)
In the present study, Lactobacillus plantarum- HDS27 strain isolated from bovine milk was used for the enhanced production of riboflavin. Riboflavin production was done and detected by Thin-layer chromatography and High-Performance Liquid Chromatography. Production medium was optimized by one factor at a time with different parameters. Statistical optimization by Response surface methodology (RSM), central composite design was used to optimise variables such as pH, temperature, glucose, and yeast extract. The present study reveals the maximum riboflavin production by one factor at a time was obtained under the culture conditions; glucose, yeast extract, pH 6, the temperature at 40℃ and 3% of inoculum size. In RSM, analysis of variance for the responses was calculated. Among the tested variables, pH, yeast extract, and temperature showed significant impact on the riboflavin production. Maximum amount of yeast extract in production medium resulted in increased riboflavin production. The riboflavin production after 24 h with the optimal condition was found to be 12.33 mg/L. It was found proximate to the expected value (12.29mg/L) achieved by the RSM model. The yield of riboflavin was increased to 3.66 fold after 24 h with the optimized parameters. The current research, emphasizes that the Lactobacillus plantarum – HDS27 could be an excellent strain for the large- scale industrial production of riboflavin